2009
DOI: 10.1136/ard.2008.098376
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal region 16p13: further evidence of increased predisposition to immune diseases

Abstract: Associations of CLEC16A polymorphisms with T1D and MS were successfully replicated in a Spanish population. A novel association of rs6498169 with a predisposition to RA was described which is consistent with previous MHC2TA results. These data provide evidence for the influence of variants within this chromosomal region on the development of complex diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 16 publications
(23 reference statements)
5
51
1
Order By: Relevance
“…12,13 Although a previous meta-analysis of published results for the rs3087456 SNP in RA patients revealed no significant association, 15 four more studies of this SNP have been published since then. 6,10,13,16 Using only the recessive model, which was strongest in both our results and the previous metaanalysis (P ¼ 0. Meta-analysis, fixed effects model; heterogeneity:…”
Section: Association Testssupporting
confidence: 62%
“…12,13 Although a previous meta-analysis of published results for the rs3087456 SNP in RA patients revealed no significant association, 15 four more studies of this SNP have been published since then. 6,10,13,16 Using only the recessive model, which was strongest in both our results and the previous metaanalysis (P ¼ 0. Meta-analysis, fixed effects model; heterogeneity:…”
Section: Association Testssupporting
confidence: 62%
“…It covers a gene of unknown function termed CLEC16A, which is expressed in antigen presenting cells and NK cells, but little else is known about this gene or its possible role in the pathogenesis of the disease. Our group replicated the association detected in the WTCCC study (Martinez et al, 2010). Here we will analyze its influence in age at onset.…”
Section: Genome-wide Associationssupporting
confidence: 62%
“…Several SNPs (rs2903692, rs17673553, rs725613 and rs12708716) within the CLEC16A gene have been shown to be associated with T1D in different populations (196,(198)(199)(200)(201)(202)(203). Dubois et al (204) recently also identified an association between the class II, major histocompatibility complex, transactivator (CIITA)-suppressor of cytokine signaling 1 (SOCS1)-CLEC16A region and CD, although it just reached borderline genome-wide significance.…”
Section: O V E M B E R -D E C E M B E R 2 0 1 1 I G a D I N A U T O Imentioning
confidence: 99%